Hubungan Pengetahuan dan Jumlah Anak dengan Sikap Pria Terhadap Keikutsertaan Terhadap KB Vasektomi - Anis Ervina; Dian Raihanah (Akademi Kebidanan La Tansa Mashiro, 2017)
The study aims at identifying the relationship among knowledge and the number of children with men’s behaviour towards their participation in vasectomy. The study uses quantitative description method. The sample taken is 90 married men who do not have any vasectomy. The data collection is gained through questionnaires. The sampling method is taken non-randomly by incorporating quota sampling. The study is taken at Kalanganyar Village during April until August 2014. The result of the study shows that 30.0% of the respondents have little knowledge and 70.0% of them have good knowledge on vasectomy. Among 42.2% of the respondents do not support the use of vasectomy, while 57.8% show their support in using vasectomy. It can be concluded that almost a half of the respondents have good knowledge on vasectomy and a half of the respondents support the use of vasectomy. It is thus essential to provide men and their wives with communication, information, and education (KIE) so that the decision to choose the most suitable contraceptive can be made together.